High coke deposition resistance by Cr loading on zeolite defects: reduced regeneration in cracking reactions. Issue 24 (18th November 2022) - Kokuryo, Shinya; Tamura, Kazuya; Miyake, Koji; Uchida, Yoshiaki; Miyamoto, Manabu; Oumi, Yasunori; Mizusawa, Atsushi; Kubo, Tadashi; Nishiyama, Norikazu
Abstract : This study is one of the few to develop a strategy that inhibits coke deposition by loading Cr on zeolite defects. We revealed that Cr 6+ species, which interacted with hydroxyl groups in the zeolite framework inhibited coke deposition. Abstract : A Cr-loaded zeolite cannot be considerably deactivated by coke deposition and can be reused for LDPE cracking without regeneration. The Cr species interact with hydroxyl groups derived from structural defects in the zeolite framework to inhibit coking. This study provides useful information on coking inhibition in various chemical industries.